Colchicine modulates calcium homeostasis and electrical property of HL‐1 cells. Issue 6 (29th February 2016) - Lu, Yen‐Yu; Chen, Yao‐Chang; Kao, Yu‐Hsun; Lin, Yung‐Kuo; Yeh, Yung‐Hsin; Chen, Shih‐Ann; Chen, Yi‐Jen
Abstract: Colchicine is a microtubule disruptor that reduces the occurrence of atrial fibrillation (AF) after an operation or ablation. However, knowledge of the effects of colchicine on atrial myocytes is limited. The aim of this study was to determine if colchicine can regulate calcium (Ca 2+ ) homeostasis and attenuate the electrical effects of the extracellular matrix on atrial myocytes. Whole‐cell clamp, confocal microscopy with fluorescence, and western blotting were used to evaluate the action potential and ionic currents of HL‐1 cells treated with and without (control) colchicine (3 nM) for 24 hrs. Compared with control cells, colchicine‐treated HL‐1 cells had a longer action potential duration with smaller intracellular Ca 2+ transients and sarcoplasmic reticulum (SR) Ca 2+ content by 10% and 47%, respectively. Colchicine‐treated HL‐1 cells showed a smaller L‐type Ca 2+ current, reverse mode sodium–calcium exchanger (NCX) current and transient outward potassium current than control cells, but had a similar ultra‐rapid activating outward potassium current and apamin‐sensitive small‐conductance Ca 2+ ‐activated potassium current compared with control cells. Colchicine‐treated HL‐1 cells expressed less SERCA2a, total, Thr17‐phosphorylated phospholamban, Cav1.2, CaMKII, NCX, Kv1.4 and Kv1.5, but they expressed similar levels of the ryanodine receptor, Ser16‐phosphorylated phospholamban and Kv4.2. Colchicine attenuated the shortening of the collagen‐induced action potential duration in HL‐1 cells. These findings suggest that colchicine modulates the atrial electrical activity and Ca 2+ regulation and attenuates the electrical effects of collagen, which may contribute to its anti‐AF activity.